Entrepreneurship-based Biotechnology Textbook; User Review - Yusuf, Muhammad; Sembiring, Dian Arisandy Eka Putra; Hendra, Robi (Universitas Syiah Kuala, 2024)
As a medium, textbooks certainly have a role in the learning environment of students, including in biotechnology lectures. This study aims to reveal the practicality of entrepreneurship-based biotechnology textbooks. The method used was descriptive analysis. Respondents consisted of students and lecturers. The data collection technique used is a questionnaire, and uses an instrument in the form of a user questionnaire sheet.Data analysis was carried out descriptively to determine the point of view of book users. The assessment results show that the textbook is categorized as very practical. The textbook is known to have fulfilled the aspects of usefulness, ease, and time of use. It is hoped that this textbook can be widely used, especially in biotechnology and entrepreneurship courses.